Northern Lights, Volume 1. - Parker, Gilbert, 1862-1932 (Salt Lake City, UT : Project Gutenberg, 2004)
"Northern Lights, Volume 1" by Gilbert Parker is a collection of stories set in the Far West, likely written in the early 20th century during the era of westward expansion and change in North America. The narrative explores the lives, struggles, and transformations of characters within this context, particularly focusing on the interactions between Indigenous peoples and European settlers. The opening chapters feature characters like Mitiahwe, a Blackfoot woman, and her husband Dingan, as well as other Indigenous and settler figures, reflecting the complicated dynamics of love, culture, and survival in a changing landscape. The opening of the book introduces the reader to Mitiahwe, who is deeply in love with her white husband, Dingan. As she contemplates the impending winter and the challenges it may bring, her mother, Swift Wing, foresees dangers in the air and warns her. The plot thickens with the arrival of Breaking Rock, a young man from her tribe, who ominously forewarns Mitiahwe that Dingan plans to abandon her and return to his own people. This moment sets off a chain of emotional turmoil for Mitiahwe, who grapples with the threat of losing her husband and the longing for a child to secure her bond with him. The story captures a poignant moment, articulating the fear of abandonment and the desire for connection amid the backdrop of cultural tension and changing times in the West. (This is an automatically generated summary.)
A lodge in the wilderness -- One at Red Man's River -- The stroke of the hour -- Buckmaster's boy.
Release date is 2004-07-01
This eBook was produced by David Widger
Keywords: Canada, Northern -- Fiction; Short stories, Canadian